Climate effects on stem radial growth of Quercus suber L.: does tree size matter?. (1st October 2018) - Mendes, Maria Paula; Cherubini, Paolo; Plieninger, Tobias; Ribeiro, Luís; Costa, Augusta
Abstract: The cork oak ( Quercus suber L.) is periodically harvested for bark (cork) throughout its lifetime. Trees undergo physiological changes as they age which affect stem diameter growth and their sensitivity to climate. However, little is known about trees age- or size-related growth changes and it remains unclear if trees of different ages (sizes) have similar climate-growth relationships. In this study, we examined the increment in stem basal area of 47 randomly selected (large and small) cork oaks over a 12-year period to assess divergent climate-growth relationships. Our approach, using a machine learning algorithm on unlabelled data sets of basal area increments, successfully filtered out tree-clusters that suggested a size (age)-dependent growth response to climate. On average, the basal area increment was more than three times larger in larger-trees clusters compared with smaller-trees clusters. A large tree (diameter >75 cm) on average added 105 cm 2 y −1 to its basal area against 25 cm 2 y −1 in a small tree (diameter <35 cm). Additionally, in smaller-trees, cork harvesting intensified the negative impact of drought on tree growth, and worsened post-drought recovery. These findings highlight the need to consider biological growth trends for accurate predictions of trees responses to drought.